Development of Foreign Competitor Identification Index (FCII) in Malaysia - Ab., Nur Izzati; ., Christopher Nigel Preece (Information Management and Business Review, 2015)
Most previous studies have dealt with foreign competitors in host country by considering how the contractors compete in international environment. The purpose of this study is to develop a foreign competitor identification index (FCII) by assessing the global orientation of international contractors in Malaysia using various characteristics. The exploratory study is based on the secondary data from Engineering News Record (ENR, 2013) and Construction Industry Development Board (CIDB, 2013) Malaysia. The sampling frame was from the ENR top 250 international contractors operating in more than 100 countries worldwide. Their involvement in international projects includes general building, manufacturing, power, water supply, sewerage/solid waste, industrial process, petroleum, transportation, hazardous waste and telecommunications. Six (6) measurements were used to develop the FCII mode which were based on number of years of experience and number of consecutive years operating in Malaysia, number of countries they are working outside Malaysia, number of projects and number of diversity of projects undertaken in Malaysia, and ranking in ENR. The data was analysed descriptively to make the comparison and establish the findings. Thirty eight (38) out of 250 top international contractors listed by the ENR have been operating in Malaysia. It was observed that that the most competitive contractor with the highest FCII score has more than 12 year of consecutive years working in Malaysia working on 99 projects, operating in more than 20 countries outside Malaysia and ranked at 17th place by the ENR (2013). The study used a sampling frame of population based on ENR. Therefore, the proposed measurements shall be further validated by the subject matter experts. The study will assist local contractors to recognize the foreign competitors in Malaysia and a competitive index model will be further developed to guide the local contractors to prepare themselves to compete with the foreign contractors in Malaysia. Neglecting to properly assess the foreign contractors’ characteristics can lead to poor performance in their local business ventures. This study intends to contribute to an improved understanding foreign contractor’s competitiveness in relation to the local contractors towards the development of the FCII model. Although there have been various models related to competitive index, there is currently no model that attempts to show the effects of foreign contractors on the local contractors.